KONSEPSI AL-QURâ€™AN TENTANG TALAK - Affandi, Abdullah (SAMAWAT: Journal Of Hadith and Qur’anic Studies, 2021)
Divorce is not for fun, and it is not an outlet for anger. As is often done by an ignorant man who easily divorces his wife over the slightest dispute. Suppose that person has abused the law of Allah SWT. for people who are given the right to divorce their wives. Even though it is given by the Shari'a to be used when in a forced state, not for any circumstances. They have made weapons to frighten and threaten women. This case is clearly proud of the aim of the Shari'a which makes divorce to straighten out the abuses and heresy of a wife or husband. With a thematic approach, this article will review the Qur'anic conception of divorce based on the interpretations of the commentators.